Rights and Obligations of Children With Special Needs in Islamic Religious Education: A Study of Tarbawi Hadith - Utami Qonita Rahmi; Elan Sumarna; Cucu Surahman (Fakultas Agama Islam Universitas Billfath, 2025)
Inclusive education in Islamic Religious Education is an important element in providing equal opportunities for Children with Special Needs. This research analyzes the rights and obligations of Children with Special Needs in Islamic Religious Education (IRE) through the perspective of educational hadiths. With a qualitative approach based on literature study, this research examines the principle of inclusivity reflected in the Prophet's hadiths, including the story of Julaibib. Data were analyzed using the Miles and Huberman method (data reduction, data presentation, and conclusion drawing). The research results show that the value of inclusivity in tarbawi hadith emphasizes equal rights to education for children with special needs, the importance of adaptive learning methods, and the role of teachers and the community in supporting inclusive education. The implications of this research emphasize the need for educator training and a curriculum based on Islamic values that appreciate diversity.